Analysis of Budget Constraints, Technical Constraints, and Institutional Integration on Performance: A Literature Review Study - Sudewo, Gatot Cahyo (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the influence of budget constraints, technical constraints, and institutional integration on performance. The method used is descriptive-qualitative, with an approach of literature review. This study synthesizes findings from various relevant internationally indexed academic articles. Data were collected from reputable internationally indexed articles obtained through databases such as Scopus, Web of Science, Emerald, Springer, and Google Scholar. The selected literature was analyzed using reduction techniques, data presentation in matrix form, and comparative synthesis to find patterns, similarities, and differences between studies. The results of the study show that Budget Constraints, Technical Constraints, and Institutional Integration affect Performance. The contribution of this study is to provide significant theoretical and practical contributions to the national transportation safety committee. The novelty of this study lies in the integration of models in analyzing the relationship between Budget Constraints, Technical Constraints, and Institutional Integration on Performance in the specific context of the National Transportation Safety Committee, which has not been widely studied in academic literature.